The Correlation of Serum NT-proBNP Levels of Hemorrhagic and Ischemic Lesions Detected with Diffusion MRI in Head Traumas - Akgun, Bekir; Erol, Fatih Serhat; Yildirim, Hanefi; Ilhan, Nevin; Kaplan, Metin (Turkish Neurosurgical Soc, 2013)
AIM: To evaluate the correlation between the dimensions of ischemic and hemorrhagic lesions detected by diffusion MRI and the changes in lesion dimensions with serum NT-proBNP levels in mild and moderate head trauma. MATERIAL and METHODS: 30 patients were assessed in our study. A control group of 10 individuals with no trauma history was formed in order to establish normal serum NT-proBNP values. Patients underwent brain diffusion MRI 24 and 48 hours following admittance. Their plasma NT-proBNP levels were checked at the same stages. RESULTS: The correlation between the values of 24th and 48th hour Intra-axial hemorrhage (IAHEM) and Intra-axial ischemia (IAISC) and the values of 24th and 48th hour NT-proBNP was established as statistically significant. CONCLUSION: It was observed that the serum NT-proBNP values could be higher in patients with wide intra-axial lesion following head trauma than patients with smaller intra-axial lesions. In addition, the fact that it has been established that the serum NT-proBNP values of patients with increasing cerebral parenchymal lesion dimensions on the advancing hours after the trauma increase suggests that serum NT-proBNP values may be significant in the follow-up of the dimensions of cerebral parenchymal damage.
Keywords: Head injuries; NT-proBNP; Diffusion MRI; Ischemia; Hemorrhage